The importance of confidence, complacency, and convenience for influenza vaccination among key risk groups in large urban areas of Peru. Issue 2 (1st February 2021) - González-Block, Miguel Ángel; Arroyo-Laguna, Juan; Rodríguez-Zea, Berenice; Pelcastre-Villafuerte, Blanca Estela; Gutiérrez-Calderón, Emilio; Díaz-Portillo, Sandra Patricia; Puentes-Rosas, Esteban; Sarti, Elsa
ABSTRACT: Influenza vaccination has been available under Peru's national immunization program since 2008, but vaccination coverage has decreased lately. Surveys and focus groups were conducted among four risk groups (pregnant women, mothers of children aged <6 years, adults with risk factors, and adults aged ≥65 years) to identify factors affecting influenza vaccine hesitancy in Peru. The 3Cs model (Confidence, Complacency, and Convenience) was used as a conceptual framework for the study. Most pregnant women and mothers of young children (70.0%), but less than half (46.3%) of older adults and adults with risk factors were vaccinated against influenza. Vaccine confidence and complacency were positively associated with educational level. Complacency was the most deficient of the 3Cs. Pregnant women and mothers were the most informed and least complacent among risk groups. Focus groups revealed the misconceptions behind the high level of complacency observed, including the perception of influenza risk and the role assigned to vaccination in preventing the disease. Interviews with officials identified that most strategies are directed to vaccination availability and hence to convenience, with opportunities for strategies to improve vaccination uptake and community engagement. The results highlight the importance of implementing in Peru communication strategies to increase perceptions of vaccine safety and effectiveness thus improving confidence and reducing complacency. The establishment of explicit incentives should also be considered to increase vaccination uptake, particularly to health personnel.